Tool and Equipment Information Management System - Kor, Wei Yan; Nureize Arbaiy (Applied Information Technology And Computer Science, 2025)
Organizations that use manual tools and equipment management systems often face security risks, data loss and inefficiencies. Issues with using manual paper-based documents for tools and equipment management include data loss, misplaced information, and human error. Therefore, the Tools and Equipment Information Management System is developed to manage and organize the information of tools and equipment in an organization. The intention is to improve the efficiency of tooling and equipment management, which will improve the overall performance of key manufacturing processes. The project approach is based on a prototype model, and the system is implemented using XAMPP, MySQL, PHP, and HTML. The new system has key functions, including updating, presenting, exporting, and importing data from the database. Additionally, it will manage vendor information, track tools, track maintenance plans, provide reports and allow access for individuals based on their roles and permissions. Finally, this information system is important because it can help firms in managing tools and equipment effectively, observing their status and condition, reducing workplace risks, reducing resource wastage and increasing productivity.